2021
DOI: 10.3389/fphys.2021.662132
|View full text |Cite
|
Sign up to set email alerts
|

Liver Transcriptome Dynamics During Hibernation Are Shaped by a Shifting Balance Between Transcription and RNA Stability

Abstract: Hibernators dramatically lower metabolism to save energy while fasting for months. Prolonged fasting challenges metabolic homeostasis, yet small-bodied hibernators emerge each spring ready to resume all aspects of active life, including immediate reproduction. The liver is the body’s metabolic hub, processing and detoxifying macromolecules to provide essential fuels to brain, muscle and other organs throughout the body. Here we quantify changes in liver gene expression across several distinct physiological sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 88 publications
1
21
1
Order By: Relevance
“…This is supported by studies in mice demonstrating that mice preconditioned with sub-lethal ischemia before more severe ischemia can increase ischemic tolerance through induction of DNA repair mechanisms 91 . To continue, when observing hibernating animals, transcriptomic studies of the liver in hibernating 13-lined ground squirrels (Ictidomys tridecemlineatus) also found enrichment of genes involved in double-strand break repair with upregulation of genes such as DDX11 that were correlated with colder body temperatures 92 . Similar observations were made by Jenson et al, who reported DNA repair-related GO terms in the liver of hibernating grizzly bears (Ursus arctos horribilis) involving serval DNA repair (e.g.…”
Section: Hypo-metabolic State Confers An Anti-apoptotic Phenotype The...mentioning
confidence: 99%
“…This is supported by studies in mice demonstrating that mice preconditioned with sub-lethal ischemia before more severe ischemia can increase ischemic tolerance through induction of DNA repair mechanisms 91 . To continue, when observing hibernating animals, transcriptomic studies of the liver in hibernating 13-lined ground squirrels (Ictidomys tridecemlineatus) also found enrichment of genes involved in double-strand break repair with upregulation of genes such as DDX11 that were correlated with colder body temperatures 92 . Similar observations were made by Jenson et al, who reported DNA repair-related GO terms in the liver of hibernating grizzly bears (Ursus arctos horribilis) involving serval DNA repair (e.g.…”
Section: Hypo-metabolic State Confers An Anti-apoptotic Phenotype The...mentioning
confidence: 99%
“…In animals, the expression or repression of certain genes modulates hibernation processes and adaptive evolution. For example, in the livers of thirteen‐lined ground squirrels, the expression of genes associated with fatty acid, cholesterol and steroid biosynthesis, xenobiotic, and amino acid metabolism were reduced 13 . In Arctic ground squirrels, high expression of Pck1 , a crucial enzyme of gluconeogenesis, coupled with low expression of Gck , was observed to improve energy distribution during hibernation 14 .…”
Section: Introductionmentioning
confidence: 99%
“…To test for tissue specificity of gene expression, we sampled three different tissues (brain, cochlea, and liver) for each individual. Brain and liver were commonly used to investigate seasonal differences in gene expression (e.g., Gillen et al, 2021 ; Johnston et al, 2016 ; Schwartz et al, 2013 ; Xiao et al, 2015 ; Zhao et al, 2016 ). In this study, we also included cochlea tissue because previous studies have indicated seasonal changes in echolocation calls and auditory processing in bats (Grilliot et al, 2014 ; Miller et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%